Human Resource Management Strategies to Enhance Teacher Competence in the Digital Era - Ricky Firmansyah; Phitsa Mauliana; Wildan Wiguna; R. Dewi Sulastriningsih; Nanang Hunaifi (Institut Teknologi Pendidikan Indonesia, 2026)
This study aims to analyze human resource management strategies in improving teacher competence in the digital era, identify the challenges faced by educational institutions, and describe strategic efforts to support continuous teacher competence development. This research employed a literature review method by examining relevant scientific journal articles published within the last five years. The findings indicate that improving teacher competence in the digital era requires systematic human resource management strategies, including competency needs identification, continuous digital training, mentoring, supervision, performance evaluation, career development, and the establishment of a collaborative learning culture. The main challenges include teachers’ limited digital literacy, inadequate technological infrastructure, lack of continuous training, and insufficient school policy support. This study emphasizes that improving teacher competence should not merely focus on technical skills in using technology, but also on integrating technology, pedagogy, and subject content through the TPACK approach. Therefore, human resource management serves as a strategic approach to developing teachers who are adaptive, professional, and innovative in responding to the demands of digital learning.